2003
DOI: 10.1046/j.1365-3040.2003.01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation in cadmium tolerance and its relationship to metal hyperaccumulation for seven populations of Thlaspi caerulescens from western Europe

Abstract: Thlaspi caerulescens J. & C. Presl is a distinctive metallophyte of central and western Europe that almost invariablyhyperaccumulates Zn to > 1.0% of shoot dry biomass in its natural habitats, and can hyperaccumulate Ni to > 0.1% when growing on serpentine soils. Populations from the Ganges region of southern France also have a remarkable ability to accumulate Cd in their shoots to concentrations well in excess of 0.01% without apparent toxicity symptoms. Because hyperaccumulation of Cd appears to be highly va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
218
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(245 citation statements)
references
References 62 publications
23
218
1
3
Order By: Relevance
“…Roosens et al (2003) further showed that the addition of Zn (10 or 100 μM) in hydroponic solutions containing Cd (30 μM) did not decrease leaf Cd concentration in SF population (also called "Ganges ecotype"), confirming the idea that Cd is accumulated independently of Zn in these populations. We tested this hypothesis for the AV population and two others by comparing the Cd concentration between the two salt mixtures (100Zn250Cd and 250Zn250Cd) and the monometallic salt 250 CdSO 4 at the same Cd concentration (250 mg Cd/kg).…”
Section: Mns Mns Mns Mns Mns Mns Mns Mns Mns Mns Mnsmentioning
confidence: 73%
See 3 more Smart Citations
“…Roosens et al (2003) further showed that the addition of Zn (10 or 100 μM) in hydroponic solutions containing Cd (30 μM) did not decrease leaf Cd concentration in SF population (also called "Ganges ecotype"), confirming the idea that Cd is accumulated independently of Zn in these populations. We tested this hypothesis for the AV population and two others by comparing the Cd concentration between the two salt mixtures (100Zn250Cd and 250Zn250Cd) and the monometallic salt 250 CdSO 4 at the same Cd concentration (250 mg Cd/kg).…”
Section: Mns Mns Mns Mns Mns Mns Mns Mns Mns Mns Mnsmentioning
confidence: 73%
“…This is in agreement with Reeves et al (2001), who showed that field-collected N. caerulescens of PW accumulated up to 6000 mg/kg, despite the fact that the soil Zn concentration was below 70 mg/kg (Table 1). In hydroponic experiments, SERP populations had higher (Roosens et al 2003) or similar (Assunção et al 2003a; values of foliar Zn concentration compared to MET populations.…”
Section: Zinc Concentration and Zinc Massmentioning
confidence: 88%
See 2 more Smart Citations
“…This may be true for both essential and non-essential elements. For instance, the hyperaccumulator Noccaea caerulescens had a 75 % increase in biomass when supplied with Cd after 31 days (Roosens et al 2003). The element Se is not known to be essential for plants, but is beneficial for the growth of many plant species, especially Se hyperaccumulators (virupaksha and Shrift 1965;el Mehdawi et al 2012).…”
Section: Which Selection Pressures Favored the Evolution Of Hyperaccumentioning
confidence: 99%